Pemanfaatan Limbah Botol Plastik Sebagai Bahan Serat Pada Beton - Syarif Hidayatullah; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research studied the mechanical properties of concrete are compressive strength, split tensile strength, flexural strength concrete that uses shredded plastic bottles as fiber. The use of this as a fiber chopped aims to reduce plastic bottle waste and improve the mechanical properties of normal concrete. The test object is cylindrical and beams, used variation is the addition of as much as 0.0%, 0.2%, 0.4%, 0.6%, 0.8% and 1.0%. The results showed the highest compressive strength of concrete on the variation of 0.6% IE 9.47% of the sum of normal concrete. For a split tensile strength experienced the highest increase at 0.6% variation in the amount of 39.53% And Strong Bending experienced highest increase in the variation of 0.8% IE 19.44% of the sum of normal concrete. The results showed the addition of Shredded 1-3 mm with a length of 5 cm Plastic Bottles as fibers in concrete mixtures can improve the mechanical properties of concrete, in particular concrete compressive strength, tensile strength of concrete sides, and flexural strength. Keywords: chopped 1-3 mm width 5cm, plastic bottles, compressive strength, tensile strength sides, flexural strength.